Method for promoting lithium pre-embedding of waste electrode material

Through mechanical activation and lithium salt addition methods, the problem of low pre-embedding of waste electrode materials in battery recycling is solved, and the lithium content is significantly increased and environmentally friendly production is achieved, and there is significant potential for industrial application.

CN119297457AActive Publication Date: 2025-01-10HARBIN INST OF TECH +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411309992.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-10
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

The prior art ignores the structural characteristics of the material itself in battery recycling, resulting in low efficiency in the regeneration process of lithium batteries and unable to effectively promote the pre-embedded lithium reaction of waste electrode materials.

Method used

The mechanical activation process induces oxygen defects on the surface of the waste electrode material and adds lithium salts to the ball mill treatment to promote the pre-embedded lithium reaction, including ball mill treatment, washing, centrifugation and drying steps, using common low-cost industrial raw materials such as deionized water and anhydrous ethanol to achieve pre-embedded lithium of the material.

Benefits of technology

The lithium content in waste electrode materials has been successfully increased by 8-11%, and through the formation of oxygen defects and the decomposition of lithium salts, the pre-embedded lithium of the electrode materials has been promoted, production costs and pollution emissions have been reduced, and there is significant industrial application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297457A_ABST
    Figure CN119297457A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, and discloses a method for promoting lithium pre-intercalation of a waste electrode material, which comprises the following steps: mixing the waste electrode material and a lithium salt, and then carrying out ball milling treatment to obtain a preliminary lithium pre-intercalation material; and washing, centrifuging and drying the preliminary lithium pre-intercalation material to obtain the lithium pre-intercalation material rich in oxygen defects. According to the method, generation of oxygen defects on the surface of the waste ternary positive electrode material is regulated and controlled in the mechanical activation process, lithium salt is further added in the mechanical activation process, lithium pre-embedding of the waste electrode material is promoted, rich oxygen defects are generated on the surface of the waste positive electrode material in the process, meanwhile, part of lithium ions are promoted to be embedded into crystal lattices of the electrode material in advance; the lithium content in the electrode material is increased, and lithium pre-embedding is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium batteries, and in particular to a method for promoting pre-embedding of lithium in waste electrode materials. Background Art

[0002] Driven by multiple ecological, social and economic factors, the field of battery recycling has made significant progress in recent years. In particular, the innovative direct regeneration strategy can be used as an ideal method to repair degraded cathode materials without destroying the materials. Compared with traditional metallurgical methods, the direct regeneration strategy shows significant advantages. With the reduction of closed-loop production costs and pollution emissions, direct lithium replenishment has become a hot topic in current research. However, previous studies often ignore the structural characteristics of the material itself. Summary of the invention

[0003] In view of this, the present invention provides a method for promoting pre-lithium embedding of waste electrode materials, utilizing the structural characteristics of the material itself, inducing oxygen defects on the surface of the waste electrode material through a mechanical activation process, and simultaneously causing a pre-lithium embedding reaction.

[0004] In order to achieve the above purpose, the following technical solutions are adopted:

[0005] In one aspect, the present invention provides a method for promoting pre-lithium insertion of waste electrode materials, comprising the following steps:

[0006] (1) mixing the waste electrode material and the lithium salt and then subjecting them to ball milling treatment to obtain a preliminary pre-embedded lithium material;

[0007] (2) washing, centrifuging and drying the preliminary pre-embedded lithium material to obtain a pre-embedded lithium material rich in oxygen defects.

[0008] Preferably, the rotation speed of the ball milling treatment is 300-500 rpm, the duration is 4-14 hours, and the ball-to-material ratio is (22-27):1.

[0009] Preferably, the lithium salt includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate.

[0010] Preferably, the molar ratio of the lithium element in the lithium salt to the transition metal element in the waste electrode material is (1-1.1):1.

[0011] Preferably, the washing is: washing with water at 60-80° C. for 3-5 times repeatedly, and then washing with anhydrous ethanol for 1-3 times repeatedly.

[0012] Preferably, the centrifugal speed is 8500-11000 rpm, and the time is 5-10 min.

[0013] Preferably, the drying is: drying in an air atmosphere at 50-80° C. for 6-12 hours.

[0014] Preferably, the waste electrode materials come from waste lithium batteries, and the waste lithium batteries include nickel-cobalt-manganese ternary lithium batteries in different proportions.

[0015] On the other hand, the present invention also provides a pre-embedded lithium material rich in oxygen defects, which is obtained by any of the above methods for promoting pre-embedded lithium in waste electrode materials, and the lithium content in the pre-embedded lithium material is increased by 8-11%.

[0016] The present invention provides a method for promoting pre-embedding lithium in waste electrode materials. Compared with the prior art, the method has the following beneficial effects:

[0017] The present invention induces oxygen defects to form on the surface of waste electrode materials under the action of mechanical force during the mechanical activation process, and simultaneously adds lithium salts during the process to promote pre-lithium insertion of waste electrode materials. The method of the present invention mainly uses common and low-cost industrial raw materials such as deionized water and anhydrous ethanol. The operation process only requires mechanical activation, and no other additives need to be added during the process. It is easy to implement in industrial production, so the present invention has strong industrial application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0019] Figure 1 The EPR images of the samples obtained after mechanical activation at different times in Example 1;

[0020] Figure 2 The XPS O1s spectrum of the material after mechanical activation and pre-lithium insertion in Example 2-8;

[0021] Figure 3 The peak area fitting result of the XPS O1s spectrum of the material after mechanical activation and pre-lithium insertion in Example 2-8;

[0022] Figure 4 This is the XPS C1s spectrum of the material after mechanical activation and pre-lithium insertion in Example 2-8;

[0023] Figure 5 The XPS Li 1s spectrum of the material after mechanical activation and pre-lithiation in Example 2-8;

[0024] Figure 6The lithium content test results of the mechanically activated pre-embedded lithium material in Example 2-8 after repeated washing. DETAILED DESCRIPTION

[0025] The present invention will be described below by specific examples, and it will be appreciated by those skilled in the art that the following specific examples are only for illustrative purposes, and do not limit the scope of the present invention in any way. In addition, in the following examples, unless otherwise specified, the reagents and equipment used are all commercially available. If in the following examples, specific treatment conditions and treatment methods are not clearly described, then conditions and methods known in the art can be used to process.

[0026] In one aspect of the present invention, the present invention provides a method for promoting pre-lithium insertion of waste electrode materials, comprising the following steps:

[0027] Step S100: Mix the waste electrode material and lithium salt and then perform ball milling to obtain a preliminary pre-embedded lithium material.

[0028] In this step, the waste electrode material comes from waste lithium batteries, and the waste lithium batteries include nickel-cobalt-manganese ternary lithium batteries with different proportions, for example, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.5 Co 0.2 Mn 0.3 O2 or LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0029] The ball milling process has a rotation speed of 300-500 rpm, preferably 350-450 rpm, a duration of 4-14 hours, preferably 8-10 hours, and a ball-to-material ratio of (22-27):1, preferably (24-25):1. The waste electrode material is mechanically activated by ball milling to induce the generation of oxygen defects. Under the above ball milling process parameters, the optimal reaction conditions for pre-embedded lithium can be determined. If the rotation speed is too high, the lithium salt raw material will be lost. If the ball milling time is too long, the pre-embedded lithium content in the material will be reduced.

[0030] The lithium salt includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate, preferably lithium hydroxide. By adding lithium salt during the mechanical activation process, the lithium salt is induced to decompose, thereby promoting the pre-embedding of lithium in the waste electrode material.

[0031] The molar ratio of the lithium element in the lithium salt to the transition metal element in the waste electrode material is (1-1.1):1, preferably 1.05:1.

[0032] The present invention triggers the formation of oxygen vacancies through a mechanical activation process, and simultaneously successfully achieves pre-lithium embedding of the material by adding lithium salts during the mechanical activation process, thereby promoting the replenishment of lattice lithium in waste materials.

[0033] Step S200: Wash, centrifuge and dry the preliminary pre-embedded lithium material to obtain a pre-embedded lithium material rich in oxygen defects.

[0034] In this step, the washing is: repeatedly washing 3-5 times with water at 60-80°C, and then repeatedly washing 1-3 times with anhydrous ethanol to remove the residual lithium salt that has not reacted; the centrifugal speed is 8500-11000rpm, and the time is 5-10min; the drying is: drying in an air atmosphere at 50-80°C for 6-12h.

[0035] On the other hand, the present invention also provides a pre-embedded lithium material rich in oxygen defects, which is obtained by the above-mentioned method for promoting pre-embedded lithium in waste electrode materials, and the lithium content in the pre-embedded lithium material is increased by 8-11%.

[0036] The process of determining the lithium content in the pre-embedded lithium material is as follows: the pre-embedded lithium material is dissolved in aqua regia, the volume is fixed to 1L with distilled water, and the lithium content in the pre-embedded lithium material is determined by inductively coupled plasma optical emission spectroscopy (ICP-OES).

[0037] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0038] Example 1

[0039] Waste ternary cathode material LiNi 0.5 Co 0.2 Mn 0.3 After O2 is calcined in air atmosphere, waste electrode materials without binder and carbon black are obtained.

[0040] 1 g of waste material was placed in a 100 mL ball mill with a ball-to-material ratio of 25:1. Mechanical activation was performed at a rotation speed of 360 rpm for 8 h. Samples were taken before the start of mechanical activation and after 4 h, and were named MA-0h, MA-4h, and MA-8h, respectively, for EPR testing.

[0041] Example 2

[0042] 1 g of waste material was put into a 100 mL ball mill, and lithium hydroxide monohydrate was added, with the stoichiometric ratio of lithium and transition metal elements being 1.05:1 and the ball-to-material ratio being 25:1. Mechanical activation was carried out at a rotation speed of 360 rpm for 2 hours to obtain a material with pre-lithium embedded for 2 hours, and an XPS test was carried out; then, the material was washed with deionized water at 60°C for 5 times, washed with anhydrous ethanol for 2 times, and centrifuged at a speed of 10,000 rpm for 8 minutes, and dried at 65°C in an air atmosphere for 10 hours; the material was dissolved in aqua regia and an ICP-OES test was carried out to determine the lithium content of the pre-lithium embedded material.

[0043] Example 3

[0044] The only difference between this embodiment and embodiment 2 is that the mechanical activation time is 4 hours, and the remaining operation steps are the same as those in embodiment 2.

[0045] Example 4

[0046] The only difference between this embodiment and embodiment 2 is that the mechanical activation time is 6 hours, and the remaining operation steps are the same as those in embodiment 2.

[0047] Example 5

[0048] The only difference between this embodiment and embodiment 2 is that the mechanical activation time is 8 hours, and the remaining operation steps are the same as those in embodiment 2.

[0049] Example 6

[0050] The only difference between this embodiment and embodiment 2 is that the mechanical activation time is 10 hours, and the remaining operation steps are the same as those in embodiment 2.

[0051] Example 7

[0052] The only difference between this embodiment and embodiment 2 is that the mechanical activation time is 12 hours, and the remaining operation steps are the same as those in embodiment 2.

[0053] Example 8

[0054] The only difference between this embodiment and embodiment 2 is that the mechanical activation time is 14 hours, and the remaining operation steps are the same as those in embodiment 2.

[0055] The present invention subjects the waste electrode material to mechanical activation treatment for 8 hours (MA-8h), and samples are taken before the reaction starts (MA-0h) and after the reaction is carried out for 4 hours (MA-4h) for electron paramagnetic resonance (EPR) testing. The results are as follows: Figure 1As shown. A typical EPR signal was detected in all samples, with its center at g = 2.003, indicating that electrons were trapped in oxygen vacancies, and the generation of oxygen vacancies would enhance the signal peak. As can be seen from the figure, with the increase of reaction time, the signal peak is significantly enhanced, indicating that the oxygen defect content on the surface of the electrode material increases significantly during the mechanical activation process.

[0056] The present invention performs X-ray photoelectron spectroscopy (XPS) tests on the unwashed materials after mechanical activation and pre-insertion of lithium in Examples 2-8, and further analyzes the chemical environment changes of the sample elements during the mechanical activation process. Figure 2 The peak area fitting results are shown in Figure 3 , C 1s spectrum Figure 4 , Li 1s spectrum Figure 5 In the O1s spectrum, the impurity oxygen (O Impurity , 531.4 eV) and lattice oxygen (O Lattice , 529.4eV), and 530.8eV belongs to the oxygen defect (O Vacancy ) peaks, and it was found that the characteristic peak of oxygen defects continued to increase during the mechanical activation process, indicating that mechanical force simultaneously induced the formation of oxygen vacancies in NCM materials; O 1s spectrum represents the surface lithium salt impurities Impurity Gradually decrease, O Vacancy The C 1s spectrum shows that CO3 2- This is the main product of the reaction between LiOH·H2O and CO2 in the air. Therefore, the content change of LiOH·H2O can be measured by CO3 2- The Li 1s spectrum shows the characteristic peak of Li-O bond in NCM positive electrode material at 54.25eV, the peak at 55.25eV belongs to Li-O- in Li2CO3 / LiOH; and the characteristic peak belonging to LiF is detected at 56.2eV. The test results show that with the increase of mechanical activation reaction time, the characteristic peaks of the material belonging to the lithium salt phase gradually weaken, accompanied by the enhancement of the characteristic peaks of lattice lithium, indicating that the mechanical activation process does induce some lithium to enter the lattice.

[0057] The material washed and dried after mechanical activation and pre-insertion of lithium in Example 2-8 was subjected to ICP-OES test. The results are shown in Figure 6After 2 hours of reaction, the molar ratio of lithium in the material increased significantly, from 0.844 to 0.875, and continued to increase from 2 hours to 10 hours, and then decreased slightly, indicating that the mechanical activation process successfully induced the decomposition of part of LiOH and pre-embedded part of lithium into the positive electrode material, intuitively proving the occurrence of the pre-embedded lithium process. After 10 hours of mechanical activation, the changes in each component tended to be stable, indicating that the pre-embedded lithium reaction was completed during this period, and the lithium content increased by about 11%.

[0058] In summary, the present invention regulates the generation of oxygen defects on the surface of waste ternary positive electrode materials during the mechanical activation process, and further adds lithium salts during the mechanical activation process to promote the pre-embedding of lithium in the waste electrode materials. This process produces abundant oxygen defects on the surface of the waste positive electrode materials, and at the same time promotes the pre-embedding of some lithium ions into the electrode material lattice, thereby increasing the lithium content in the electrode material and achieving pre-embedding of lithium.

[0059] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for promoting pre-lithium insertion of waste electrode materials, characterized in that: The following steps are involved: (1) mixing the waste electrode material and the lithium salt and then subjecting them to ball milling treatment to obtain a preliminary pre-embedded lithium material; (2) washing, centrifuging and drying the preliminary pre-embedded lithium material to obtain a pre-embedded lithium material rich in oxygen defects.

2. The method for promoting pre-lithium insertion of waste electrode materials according to claim 1, characterized in that: The rotation speed of the ball milling treatment is 300-500 rpm, the duration is 4-14 hours, and the ball-to-material ratio is (22-27):

1.

3. The method for promoting pre-lithium insertion of waste electrode materials according to claim 1, characterized in that: The lithium salt includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate.

4. The method for promoting pre-lithium embedding of waste electrode materials according to claim 1 or 3, characterized in that: The molar ratio of the lithium element in the lithium salt to the transition metal element in the waste electrode material is (1-1.1):

1.

5. The method for promoting pre-lithium insertion of waste electrode materials according to claim 1, characterized in that: The washing comprises: repeatedly washing 3-5 times with water at 60-80° C., and then repeatedly washing 1-3 times with anhydrous ethanol.

6. The method for promoting pre-lithium insertion of waste electrode materials according to claim 1, characterized in that: The centrifugal speed is 8500-11000 rpm, and the time is 5-10 min.

7. The method for promoting pre-lithium insertion of waste electrode materials according to claim 1, characterized in that: The drying step is: drying in an air atmosphere at 50-80° C. for 6-12 hours.

8. The method for promoting pre-lithium insertion of waste electrode materials according to any one of claims 1 to 7, characterized in that: The waste electrode materials come from waste lithium batteries, and the waste lithium batteries include nickel-cobalt-manganese ternary lithium batteries with different proportions.

9. A pre-embedded lithium material rich in oxygen defects, characterized in that: The method for promoting pre-embedding of lithium in waste electrode materials according to any one of claims 1 to 8 is adopted, and the lithium content in the pre-embedding lithium material is increased by 8-11%.

Citation Information

Patent Citations

  • Preparation method of modified high-capacity long-life ternary positive electrode material

    CN111403727A

  • Method for removing and converting surface impurities of positive electrode material of waste lithium battery

    CN116190819A

  • Method for manufacturing positive electrode active material for lithium ion secondary battery

    JP2017204340A